Interventions for the management of malignant pleural effusions: an updated network meta-analysis. (5th May 2021) - Dipper, Alex; Jones, Hayley E.; Bhatnagar, Rahul; Preston, Nancy J.; Maskell, Nick; Clive, Amelia
Malignant pleural effusion (MPE) is a commonly encountered clinical problem, causing disabling breathlessness and affecting up to 15% of all patients with cancer [1]. Wider availability of indwelling pleural catheters (IPCs) and recent development of different IPC drainage strategies has expanded the range of treatment approaches. Incorporating results from several high quality, large randomised controlled trials (RCTs), we have updated the 2016 Cochrane review [2] to determine the efficacy of different interventions for MPE. We performed a multiple interventions systematic review, pairwise meta-analyses and network meta-analyses (NMA) with the primary outcome of pleurodesis success. Secondary outcomes included adverse events, breathlessness, quality of life, cost, mortality, survival, duration of inpatient stay and patient acceptability [3]. Here, we summarise key findings of the review to increase accessibility of the "take home" messages among the wider respiratory community. Talc slurry and poudrage are effective pleurodesis agents. IPCs have lower pleurodesis rates but comparable breathlessness control and reduced risk of repeat invasive procedures. It is essential that patients have access to a range of treatment strategies. https://bit.ly/38v30yw